Membrane Proteocomplexome of Campylobacter jejuni Using 2-D Blue Native/SDS-PAGE Combined to Bioinformatics Analysis - Guérin, Alizée; Sulaeman, Sheiam; Coquet, Laurent; Ménard, Armelle; Barloy-Hubler, Frédérique; Dé, Emmanuelle; Tresse, Odile (Frontiers in Microbiology, 2020)
Campylobacter is the leading cause of human bacterial foodborne infections in developed countries. The perception cues from biotic or abiotic environments by the bacteria are often related to bacterial surface and membrane proteins that mediate the cellular response for the adaptation of Campylobacter jejuni to the environment. These proteins function rarely as a unique entity, they are often organized in functional complexes. In C. jejuni, these complexes are not fully identified and some of them remain unknown. To identify putative functional multi-subunit entities at the membrane subproteome level of C. jejuni, a holistic non a priori method was addressed using two-dimensional blue native /Sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (PAGE) in strain C. jejuni 81-176. Couples of acrylamide gradient/migration-time, membrane detergent concentration and hand-made strips were optimized to obtain reproducible extraction and separation of intact membrane protein complexes (MCPs). MCPs were subsequently denatured using SDS-PAGE and each spot from each MCP was identified by mass spectrometry. Altogether, 21 MPCs could be detected including multihomooligomeric and multiheteroligomeric complexes distributed in both inner and outer membranes. Function, conservation and regulation of MPCs across C. jejuni strains were inspected by functional and genomic comparison analyses. In this study, relatedness between subunits of two efflux pumps, CmeABC and MacABputC was observed. In addition, a consensus sequence CosR-binding box in promoter regions of MacABputC was identified in C. jejuni but not in C. coli. The MPCs identified in C. jejuni 81-176 membrane are involved in protein folding, molecules trafficking, oxidative phosphorylation, membrane structuration, peptidoglycan biosynthesis, motility and chemotaxis, stress signaling, efflux pumps and virulence.